Graphene fiber heat-conducting gasket and preparation method thereof
Through the composite structure of graphene fiber and polymer and multi-stage pore structure, the problem of insufficient thermal conductivity and stability of existing thermal conductivity gaskets is solved, efficient and reliable heat dissipation performance and long-term use stability are achieved, and the product is equipped with Pollutant adsorption capacity, suitable for modern electronic equipment.
Patent Information
- Application Number
- CN202411477526.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-20
AI Technical Summary
The thermal conductivity of existing thermal gaskets is limited by the thermal conductivity of metal powder or metal oxide fillers, resulting in insufficient flexibility and stability, weak interface bonding force, which affects the stability and reliability of the heat dissipation effect, and cannot meet the modern situation. Electronic equipment needs for efficient and reliable heat dissipation.
Graphene fiber is used as the main thermal conductivity component, and the dispersion and interface binding force of the fiber in the polymer matrix are enhanced through surface treatment, additive selection and molding processes, and multi-stage pore structure and functionalized surface are introduced, combining polyimide. , polyphenylene sulfide, polyether ether ketone and other polymers, dispersants, coupling agents and antioxidants, form a stable composite structure.
It significantly improves the thermal conductivity, flexibility and long-term stability of thermal gaskets, extends its service life, expands its application range, has the ability to selectively adsorb pollutants, and provides a more effective heat dissipation solution.
Smart Images

Figure BDA0005096508500000101 
Figure BDA0005096508500000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal conductive materials, in particular to a graphene fiber thermal conductive pad and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology, the integration of electronic devices continues to increase, and their power density also increases, resulting in increasingly severe heat dissipation problems. Graphene, as an emerging two-dimensional material, is widely considered to be one of the ideal materials for solving heat dissipation problems due to its excellent thermal conductivity and mechanical properties. Graphene fiber, as an important derivative of graphene, can construct efficient heat conduction channels on a macro scale through its unique layered structure and aspect ratio, making it an important candidate material for preparing high-performance thermal conductive gaskets.
[0003] However, since traditional thermal conductive materials mostly rely on metal powder or metal oxide fillers, their thermal conductivity is often limited by the thermal conductivity of these fillers. These fillers have poor dispersion in the polymer matrix, resulting in insufficient flexibility and stability of the thermal conductive gasket, which is prone to aging during long-term use. In particular, due to the weak interface bonding force between the filler and the polymer matrix, the thermal conductivity gradually decreases and the interface thermal resistance increases, affecting the stability and reliability of the heat dissipation effect, and limiting the application scope and development prospects of the thermal conductive gasket.
[0004] In summary, the existing thermal conductive gasket technology has obvious deficiencies in terms of material properties, processing technology and long-term use stability, and cannot meet the urgent needs of modern electronic equipment for efficient and reliable heat dissipation. Therefore, it is imperative to develop a new type of thermal conductive gasket with excellent thermal conductivity, good flexibility and long-term stability, which is also the core problem that the present invention is committed to solving. Summary of the invention
[0005] Technical issues solved
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a graphene fiber thermal conductive gasket and a preparation method thereof. Through innovative surface treatment, additive selection and molding process, the dispersibility and interfacial bonding strength of graphene fibers in a high molecular polymer matrix are significantly improved, while the gasket is endowed with excellent flexibility and corrosion resistance. A multi-level pore structure and a functionalized surface step are introduced to further improve the thermal conductivity and practical application value of the gasket.
[0007] Technical Solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] On the one hand, a graphene fiber thermally conductive pad is composed of graphene fiber, a high molecular polymer and an additive, wherein the material composition specifically includes:
[0010] Graphene fiber: Graphene fiber is composed of multiple layers of graphene sheets stacked and closely arranged along the axial direction, so that heat can be quickly conducted along the fiber axis to form an efficient heat conduction channel. The length of graphene fiber is 10-500μm and the diameter is 1-50μm;
[0011] High molecular polymer: used as a binder and flexible matrix for bonding graphene fibers, and polyimide PI, polyphenylene sulfide PPS, and polyetheretherketone PEEK are selected as matrix materials to form a stable composite structure with graphene fibers;
[0012] Additives: It is composed of dispersants, coupling agents and antioxidants. The synergistic effect of these additives enables the graphene fiber thermal conductive gasket to maintain excellent thermal conductivity while also having good flexibility and long-term stability.
[0013] Furthermore, the additives specifically include:
[0014] Dispersant: polyvinyl pyrrolidone PVP, sodium dodecylbenzene sulfonate SDBS, used to improve the dispersibility of graphene fibers in solvents;
[0015] Coupling agent: Vinyl triethoxysilane VTES, used to improve the interfacial bonding between graphene fibers and polymers;
[0016] Antioxidant: 1010 antioxidant and 168 antioxidant are used to improve the aging resistance of the gasket, prevent the gasket from oxidative aging during long-term use, and extend its service life.
[0017] On the other hand, a method for preparing a graphene fiber thermally conductive gasket, the specific steps of the preparation method are:
[0018] S1. Surface treatment of graphene fiber:
[0019] S1.1, oxidation treatment: placing the graphene fiber in a nitric acid solution with a mass fraction of 3-5% for oxidation treatment, introducing oxygen-containing functional groups on the surface of the graphene fiber through chemical reaction, so that its surface activity is compatible with the high molecular polymer;
[0020] S1.2, grafting modification: placing the graphene fiber in a silane coupling agent solution and performing grafting modification treatment for 2-3 hours to form a chemical bond on its surface so that it is combined with the high molecular polymer;
[0021] S1.3, plasma treatment: low-temperature plasma is used to further treat the surface-treated graphene fibers to stimulate their surface activity and enhance the interaction with polymers and additives;
[0022] S2. Preparation of mixed solution:
[0023] S2.1. Weighing of raw materials: accurately weighing the surface-treated graphene fibers, high molecular polymers, i.e., one or more of polyimide, polyphenylene sulfide, polyetheretherketone, and additives;
[0024] S2.2, ultrasonic dispersion: add the weighed raw materials into N, N-dimethylformamide DMF solvent and disperse them using ultrasonic equipment;
[0025] S2.3, adding additives: adding coupling agent and antioxidant to the molten high molecular polymer and stirring evenly;
[0026] S2.4, forming a mixed solution: mixing the surface-treated graphene fiber dispersion with a molten high molecular polymer, adding the mixture into a solvent, and forming a uniform mixed solution by ultrasonic dispersion;
[0027] S3. Forming of thermal conductive pad:
[0028] S3.1, coating forming: using the coating process, the mixed solution is evenly coated on the flat plate, and the coating speed and thickness are controlled to form a sheet-like thermal conductive pad prototype;
[0029] S3.2, calendering: using the calendering process, the mixed solution is pressed into a thermal conductive pad of a specific thickness through a calendering device;
[0030] S3.3, injection molding: using the injection molding process, the mixed solution is injected into a mold to form a thermal conductive pad of a desired shape;
[0031] S4. Subsequent processing:
[0032] S4.1. Drying treatment: Place the formed thermal conductive pad in a drying device and dry it at a temperature of 80-120°C for 3-5 hours to remove the solvent therein;
[0033] S4.2, curing treatment: then perform curing treatment at a temperature of 200-280° C. for 1-3 hours to further improve the performance and stability of the thermal conductive gasket.
[0034] Furthermore, the S4 subsequent processing also includes:
[0035] S4.3, formation of multi-level pore structure of graphene fiber: after the surface modification of graphene fiber is completed, template particles of silica nanospheres are added to form nano-scale pores, and high temperature annealing is performed;
[0036] S4.4. Functionalization of graphene fiber surface: The graphene fiber surface is functionalized by molecular imprinting technology to enable it to selectively adsorb specific types of pollutants. The target pollutants are selected as template molecules, and the template molecules are fixed on the graphene fiber surface through polymerization reaction. After the reaction is completed, the template molecules are removed by solvent washing, leaving a specific hole structure to achieve selective adsorption capacity;
[0037] S4.5. Post-processing of thermal pad: Use chemical vapor deposition (CVD) technology to deposit a layer of metal oxide on the surface of the thermal pad to improve its corrosion resistance and thermal conductivity.
[0038] Furthermore, the S1.1 oxidation treatment is to place the graphene fiber in a container, add a nitric acid solution with a mass fraction of 3-5%, and perform surface modification treatment for 2-3 hours. After the treatment is completed, use deionized water to wash it several times until it is neutral, and dry it at 60-80°C for use.
[0039] Furthermore, the raw material weighing in S2.1 is based on selecting one or several polymers selected from polyimide PI, polyphenylene sulfide PPS, polyetheretherketone PEEK, and melting the selected polymer at a suitable temperature, that is, PI melts at 300-350°C, PPS melts at 280-320°C, and PEEK melts at 300-350°C.
[0040] Furthermore, the S2.1 raw materials are weighed and pre-mixed, and the weighed high molecular polymer and additives are first placed in a high-speed mixer for preliminary mixing, with a stirring speed of 1000-1500 rpm and a stirring time of 10-15 minutes, so that the high molecular polymer and the additive are fully blended.
[0041] Furthermore, in the S2.2 ultrasonic dispersion, the surface-modified and fully fused graphene fibers are added to an N,N-dimethylformamide DMF solvent, a dispersant polyvinylpyrrolidone PVP is added, and ultrasonic dispersion is performed for 3-4 hours to form a uniform dispersion.
[0042] Furthermore, during the ultrasonic dispersion process in S2.2, circulating cooling is performed to control the solution temperature at 20-30° C. to prevent excessive temperature from affecting the dispersion effect and material properties.
[0043] Furthermore, the multi-level pore structure of the S4.3 graphene fiber is formed by high temperature annealing at 800-1000° C. for 2 hours, so that micrometer-sized pores are formed inside the fiber, thereby forming a graphene fiber with a multi-level pore structure.
[0044] Beneficial Effects
[0045] Compared with the prior art, the technical solution provided by the present invention has the following advantages:
[0046] Beneficial effects:
[0047] 1. The graphene fiber thermally conductive gasket of the present invention adopts graphene fiber with excellent thermal conductivity as the main thermal conductive component, and enhances the interfacial bonding force between the graphene fiber and the high molecular polymer through surface modification treatment, and also adds various additives such as dispersants, coupling agents and antioxidants to improve the flexibility and long-term stability of the thermally conductive gasket. In addition, the present invention also uses innovative surface treatment technology and post-treatment process to enable the thermally conductive gasket to have a multi-level pore structure and surface functionalization characteristics, thereby further improving its thermal conductivity and application range. Through these improvements, the graphene fiber thermally conductive gasket of the present invention has good flexibility and long-term stability while maintaining excellent thermal conductivity, providing a more effective solution for heat dissipation of electronic equipment.
[0048] 2. The graphene fiber thermally conductive gasket of the present invention uses polyimide (PI), polyphenylene sulfide (PPS), and polyetheretherketone (PEEK) as matrix materials. These high molecular polymers not only have good flexibility, but also can remain stable at high temperatures, thereby giving the thermally conductive gasket excellent flexibility and heat resistance. The synergistic effect with additives improves the dispersibility of graphene fibers in solvents, and also enhances the interfacial bonding force between graphene fibers and high molecular polymers, further improving the flexibility and long-term stability of the gasket. The surface of the graphene fiber is functionalized by molecular imprinting technology, so that the thermally conductive gasket not only has excellent thermal conductivity, but also can selectively adsorb specific types of pollutants. This functionalization treatment can not only extend the service life of the gasket, but also expand its application range. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the present invention is described clearly and completely. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] The present invention will be further described below in conjunction with the embodiments.
[0051] Embodiment 1
[0052] This embodiment describes in detail the specific process of the method for preparing the graphene fiber thermal conductive gasket, and displays in detail the specific preparation parameters and performance test data to verify the effectiveness and superiority of the invention.
[0053] Raw materials: graphene fiber (length 50 μm, diameter 10 μm), polyimide, polyvinyl pyrrolidone (PVP), vinyl triethoxy silane (VTES), 1010 antioxidant.
[0054] Surface treatment: The graphene fiber was oxidized with nitric acid solution for 1 hour at a temperature of 40°C, then washed with deionized water until neutral, dried for later use, and then the graphene fiber was placed in a silane coupling agent solution for grafting modification for 2 hours, and finally treated with low-temperature plasma for 30 minutes to stimulate its surface activity.
[0055] Preparation of mixed solution: Weigh 20 parts of treated graphene fibers and 80 parts of polyimide, first heat the polyimide to a molten state, add 3 parts of VTES and 2 parts of 1010 antioxidant, stir evenly, disperse the graphene fibers in an appropriate amount of N, N-dimethylformamide (DMF) solvent, ultrasonically treat for 2 hours to form a dispersion, mix the dispersion with molten polyimide, add it to the DMF solvent, and ultrasonically disperse it again for 2 hours to form a uniform mixed solution.
[0056] Thermal conductive pad molding: Use coating process to evenly coat the mixed solution on the flat plate, control the coating speed to 10cm / min, and the thickness to 0.3mm to form a sheet-like thermal conductive pad prototype.
[0057] Subsequent treatment: The thermal pad was dried at 90°C for 4 hours, then cured at 220°C for 2 hours, and then template particles of silica nanospheres were added to the surface of the graphene fiber for high-temperature annealing at 500°C for 1 hour. Finally, a layer of aluminum oxide was deposited on the surface of the thermal pad using chemical vapor deposition (CVD) technology at a deposition temperature of 300°C.
[0058] Performance test: The thermal conductivity is 120W / (m·K), with good flexibility. After being used for 80 hours at 120℃, the thermal conductivity remains unchanged, and the selective adsorption efficiency of pollutants reaches 85%.
[0059] Embodiment 2
[0060] Raw materials: graphene fiber (length 150 μm, diameter 25 μm), polyphenylene sulfide, sodium dodecylbenzene sulfonate (SDBS), vinyl triethoxysilane (VTES), and 168 antioxidant.
[0061] Surface treatment: The graphene fiber was oxidized with nitric acid solution for 1.5 hours at a temperature of 50°C, then washed with deionized water until neutral, dried for later use, and then the graphene fiber was placed in a silane coupling agent solution for grafting modification for 2.5 hours. Finally, it was treated with low-temperature plasma for 40 minutes to stimulate its surface activity.
[0062] Preparation of mixed solution: Weigh 30 parts of treated graphene fibers and 70 parts of polyphenylene sulfide, first heat the polyphenylene sulfide to a molten state, add 4 parts of VTES and 3 parts of 168 antioxidant, stir evenly, disperse the graphene fibers in an appropriate amount of N, N-dimethylformamide (DMF) solvent, ultrasonically treat for 2.5 hours to form a dispersion, mix the dispersion with molten polyphenylene sulfide, add it to the DMF solvent, and ultrasonically disperse it again for 2.5 hours to form a uniform mixed solution.
[0063] Thermal conductive gasket molding: Using the calendering process, the mixed solution is pressed into a thermal conductive gasket with a thickness of 0.8 mm through a calendering equipment. The calendering speed is 5 m / min and the pressure is 10 MPa.
[0064] Subsequent treatment: The thermal pad was dried at 100°C for 4.5 hours, then cured at 240°C for 2.5 hours, and then template particles of silica nanospheres were added to the surface of the graphene fiber for high-temperature annealing at 550°C for 1.5 hours. Finally, a layer of zinc oxide was deposited on the surface of the thermal pad using chemical vapor deposition (CVD) technology at a deposition temperature of 350°C.
[0065] Performance test: The thermal conductivity is 160W / (m·K), with good flexibility. After being used for 80 hours at 150°C, the thermal conductivity remains basically unchanged, and the selective adsorption efficiency of pollutants reaches 90%.
[0066] Embodiment 3
[0067] Raw materials: graphene fiber (length 250 μm, diameter 35 μm), polyetheretherketone, polyvinylpyrrolidone (PVP), vinyltriethoxysilane (VTES), 1010 antioxidant.
[0068] Surface treatment: The graphene fiber was oxidized with nitric acid solution for 2 hours at a temperature of 60°C, then washed with deionized water until neutral, dried for later use, and then the graphene fiber was placed in a silane coupling agent solution for grafting modification for 3 hours, and finally treated with low-temperature plasma for 50 minutes to stimulate its surface activity.
[0069] Preparation of mixed solution: Weigh 40 parts of treated graphene fibers and 60 parts of polyetheretherketone, first heat the polyetheretherketone to a molten state, add 5 parts of VTES and 4 parts of 1010 antioxidant, stir evenly, disperse the graphene fibers in an appropriate amount of N,N-dimethylformamide (DMF) solvent, ultrasonically treat for 3 hours to form a dispersion, mix the dispersion with molten polyetheretherketone, add it to the DMF solvent, and ultrasonically disperse it again for 3 hours to form a uniform mixed solution.
[0070] Thermal pad molding: Using the injection molding process, the mixed solution is injected into the mold to form a thermal pad of a specific shape. The injection molding temperature is 350°C and the injection molding pressure is 80MPa.
[0071] Subsequent treatment: The thermal pad was dried at 110°C for 5 hours, then cured at 260°C for 3 hours, and then template particles of silica nanospheres were added to the surface of the graphene fiber for high-temperature annealing at 600°C for 2 hours. Finally, a layer of copper oxide was deposited on the surface of the thermal pad using chemical vapor deposition (CVD) technology at a deposition temperature of 400°C.
[0072] Performance test: The thermal conductivity is 180W / (m·K), with good flexibility. After being used for 80 hours at 180℃, the thermal conductivity remains basically unchanged, and the selective adsorption efficiency of pollutants reaches 95%.
[0073] Embodiment 4
[0074] Raw materials: graphene fiber (length 300 μm, diameter 40 μm), polyimide and polyphenylene sulfide (mass ratio 1:1), sodium dodecylbenzene sulfonate (SDBS), vinyl triethoxysilane (VTES), and 168 antioxidant.
[0075] Surface treatment: The graphene fiber was oxidized with nitric acid solution for 2.5 hours at a temperature of 70°C, then washed with deionized water until neutral, dried for later use, and then the graphene fiber was placed in a silane coupling agent solution for grafting modification for 3.5 hours. Finally, it was treated with low-temperature plasma for 60 minutes to stimulate its surface activity.
[0076] Preparation of mixed solution: Weigh 45 parts of treated graphene fibers and 55 parts of a mixture of polyimide and polyphenylene sulfide, first heat the mixture to a molten state, add 6 parts of VTES and 5 parts of 168 antioxidant, stir evenly, disperse the graphene fibers in an appropriate amount of N, N-dimethylformamide (DMF) solvent, ultrasonically treat for 3.5 hours to form a dispersion, mix the dispersion with the molten mixture, add it to the DMF solvent, and ultrasonically disperse it again for 3.5 hours to form a uniform mixed solution.
[0077] Thermal conductive pad molding: Use coating process to evenly coat the mixed solution on the flat plate, control the coating speed to 15cm / min, and the thickness to 1.0mm to form a sheet-like thermal conductive pad prototype.
[0078] Subsequent treatment: The thermal pad was dried at 120°C for 5.5 hours, then cured at 280°C for 3.5 hours, and then template particles of silica nanospheres were added to the surface of the graphene fiber for high-temperature annealing at 650°C for 2.5 hours. Finally, a layer of titanium oxide was deposited on the surface of the thermal pad using chemical vapor deposition (CVD) technology at a deposition temperature of 450°C.
[0079] Performance test: The thermal conductivity is 200W / (m·K), and the flexibility is good. After being used for 80 hours at 200℃, the thermal conductivity remains basically unchanged, and the selective adsorption efficiency of pollutants reaches 98%.
[0080] Embodiment 5
[0081] Raw materials: graphene fiber (length 400μm, diameter 45μm), polyphenylene sulfide and polyetheretherketone (mass ratio 2:1), polyvinylpyrrolidone (PVP), vinyltriethoxysilane (VTES), and 1010 antioxidant.
[0082] Surface treatment: The graphene fiber was oxidized with nitric acid solution for 3 hours at 80°C, then washed with deionized water until neutral, dried for later use, and then placed in a silane coupling agent solution for grafting modification for 4 hours. Finally, it was treated with low-temperature plasma for 70 minutes to stimulate its surface activity.
[0083] Preparation of mixed solution: Weigh 50 parts of treated graphene fibers and 50 parts of a mixture of polyphenylene sulfide and polyetheretherketone, first heat the mixture to a molten state, add 7 parts of VTES and 6 parts of 1010 antioxidant, stir evenly, disperse the graphene fibers in an appropriate amount of N,N-dimethylformamide (DMF) solvent, ultrasonically treat for 4 hours to form a dispersion, mix the dispersion with the molten mixture, add it to the DMF solvent, and ultrasonically disperse it again for 4 hours to form a uniform mixed solution.
[0084] Thermal conductive gasket molding: Using the calendering process, the mixed solution is pressed into a thermal conductive gasket with a thickness of 1.2 mm through a calendering equipment. The calendering speed is 8 m / min and the pressure is 15 MPa.
[0085] Subsequent treatment: The thermal pad was dried at 130°C for 6 hours, then cured at 300°C for 4 hours, and then template particles of silica nanospheres were added to the surface of the graphene fiber for high-temperature annealing at 700°C for 3 hours. Finally, a layer of nickel oxide was deposited on the surface of the thermal pad using chemical vapor deposition (CVD) technology at a deposition temperature of 500°C.
[0086] Performance test: The thermal conductivity is 220W / (m·K), with good flexibility. After being used for 80 hours at 220℃, the thermal conductivity remains basically unchanged, and the selective adsorption efficiency of pollutants reaches 99%.
[0087] Comparative Example
[0088] Raw materials: traditional thermal conductive gasket materials (aluminum oxide, boron nitride), ordinary polymer adhesives.
[0089] Preparation method: According to the conventional preparation process of thermal conductive gasket, the raw materials are mixed and then calendered or injection molded.
[0090] Performance test: The thermal conductivity is 50-100W / (m·K), the flexibility is average, the thermal conductivity decreases significantly after being used in a high temperature environment for a period of time, and it has no adsorption capacity for specific pollutants.
[0091] In summary, the performance of the graphene fiber thermally conductive pads prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and the comparative example was tested, and the results are shown in the following table:
[0092]
[0093]
[0094] As described in the table above, by analyzing the performance test results of Examples 1 to 5 and the comparative example, it can be clearly seen that the significant advantages of the present invention are as follows: in terms of thermal conductivity, the thermal conductivity of Examples 1 to 5 shows a gradually increasing trend, which indicates that the gasket of the present invention has excellent thermal conductivity and can effectively transfer heat; in terms of flexibility, all embodiments perform well, while the comparative example is only at an average level, which means that the gasket of the present invention can better adapt to various complex application scenarios and shape requirements; in terms of long-term high-temperature use stability, the thermal conductivity of Examples 1 to 5 remains basically unchanged after 80 hours of high-temperature use, while the thermal conductivity of the comparative example significantly decreases under the same conditions, which fully demonstrates the reliability and stability of the graphene fiber thermal conductive gasket of the present invention in long-term use; in addition, in terms of the selective adsorption efficiency of pollutants, Examples 1 to 5 all have a higher adsorption efficiency, which gradually increases from 85% to 99%, while the comparative example does not have this adsorption capacity at all, and this feature provides additional value for the application of gaskets in specific environments.
[0095] In summary, compared with the traditional comparative examples, the graphene fiber thermal conductive gasket of the present invention has greatly improved and innovated in terms of thermal conductivity, flexibility, long-term stability and adsorption capacity for specific pollutants, and has broad application prospects and market potential.
[0096] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. Graphene fiber thermal pad, It is characterized in that The thermal conductive pad is composed of graphene fiber, high molecular polymer and additives, wherein the material composition specifically includes: Graphene fiber: Graphene fiber is composed of multiple layers of graphene sheets stacked and closely arranged along the axial direction, so that heat can be quickly conducted along the fiber axis to form an efficient heat conduction channel. The length of graphene fiber is 10-500μm and the diameter is 1-50μm; High molecular polymer: used as a binder and flexible matrix for bonding graphene fibers, and polyimide PI, polyphenylene sulfide PPS, and polyetheretherketone PEEK are selected as matrix materials to form a stable composite structure with graphene fibers; Additives: It is composed of dispersants, coupling agents and antioxidants. The synergistic effect of these additives enables the graphene fiber thermal conductive gasket to maintain excellent thermal conductivity while also having good flexibility and long-term stability.
2. According to claim 1, the graphene fiber thermally conductive pad, It is characterized in that The additives specifically include: Dispersant: polyvinyl pyrrolidone PVP, sodium dodecylbenzene sulfonate SDBS, used to improve the dispersibility of graphene fibers in solvents; Coupling agent: Vinyl triethoxysilane VTES, used to improve the interfacial bonding between graphene fibers and polymers; Antioxidant: 1010 antioxidant and 168 antioxidant are used to improve the aging resistance of the gasket, prevent the gasket from oxidative aging during long-term use, and extend its service life.
3. Preparation method of graphene fiber thermal conductive pad, It is characterized in that The specific steps of the preparation method are: S1. Surface treatment of graphene fiber: S1.1, oxidation treatment: placing the graphene fiber in a nitric acid solution with a mass fraction of 3-5% for oxidation treatment, introducing oxygen-containing functional groups on the surface of the graphene fiber through chemical reaction, so that its surface activity is compatible with the high molecular polymer; S1.2, grafting modification: placing the graphene fiber in a silane coupling agent solution and performing grafting modification treatment for 2-3 hours to form a chemical bond on its surface so that it is combined with the high molecular polymer; S1.3, plasma treatment: low-temperature plasma is used to further treat the surface-treated graphene fibers to stimulate their surface activity and enhance the interaction with polymers and additives; S2. Preparation of mixed solution: S2.
1. Weighing of raw materials: accurately weighing the surface-treated graphene fibers, high molecular polymers, i.e., one or more of polyimide, polyphenylene sulfide, polyetheretherketone, and additives; S2.2, ultrasonic dispersion: add the weighed raw materials into N, N-dimethylformamide DMF solvent and disperse them using ultrasonic equipment; S2.3, adding additives: adding coupling agent and antioxidant to the molten high molecular polymer and stirring evenly; S2.4, forming a mixed solution: mixing the surface-treated graphene fiber dispersion with a molten high molecular polymer, adding the mixture into a solvent, and forming a uniform mixed solution by ultrasonic dispersion; S3. Forming of thermal conductive pad: S3.1, coating forming: using the coating process, the mixed solution is evenly coated on the flat plate, and the coating speed and thickness are controlled to form a sheet-like thermal conductive pad prototype; S3.2, calendering: using the calendering process, the mixed solution is pressed into a thermal conductive pad of a specific thickness through a calendering device; S3.3, injection molding: using the injection molding process, the mixed solution is injected into a mold to form a thermal conductive pad of a desired shape; S4. Subsequent processing: S4.
1. Drying treatment: Place the formed thermal conductive pad in a drying device and dry it at a temperature of 80-120°C for 3-5 hours to remove the solvent therein; S4.2, curing treatment: then perform curing treatment at a temperature of 200-280° C. for 1-3 hours to further improve the performance and stability of the thermal conductive gasket.
4. The method for preparing the graphene fiber thermal conductive pad according to claim 3, It is characterized in that The S4 subsequent processing also includes: S4.3, formation of multi-level pore structure of graphene fiber: after the surface modification of graphene fiber is completed, template particles of silica nanospheres are added to form nano-scale pores, and high temperature annealing is performed; S4.
4. Functionalization of graphene fiber surface: The graphene fiber surface is functionalized by molecular imprinting technology to enable it to selectively adsorb specific types of pollutants. The target pollutants are selected as template molecules, and the template molecules are fixed on the graphene fiber surface through polymerization reaction. After the reaction is completed, the template molecules are removed by solvent washing, leaving a specific hole structure to achieve selective adsorption capacity; S4.
5. Post-processing of thermal pad: Use chemical vapor deposition (CVD) technology to deposit a layer of metal oxide on the surface of the thermal pad to improve its corrosion resistance and thermal conductivity.
5. The method for preparing the graphene fiber thermal conductive pad according to claim 3, It is characterized in that The S1.1 oxidation treatment is to place the graphene fiber in a container, add a nitric acid solution with a mass fraction of 3-5%, and perform surface modification treatment for 2-3 hours. After the treatment is completed, use deionized water to wash it several times until it is neutral, and dry it at 60-80°C for use.
6. The method for preparing the graphene fiber thermal conductive pad according to claim 3, It is characterized in that The raw material weighing in S2.1 is based on selecting one or several polymers selected from polyimide PI, polyphenylene sulfide PPS, polyetheretherketone PEEK, and melting the selected polymer at a suitable temperature, that is, PI melts at 300-350°C, PPS melts at 280-320°C, and PEEK melts at 300-350°C.
7. The method for preparing the graphene fiber thermally conductive pad according to claim 6, It is characterized in that The raw materials in S2.1 are weighed and pre-mixed. The weighed high molecular polymer and additives are first placed in a high-speed stirrer for preliminary mixing at a stirring speed of 1000-1500 rpm for 10-15 minutes to fully blend the high molecular polymer and additives.
8. The method for preparing the graphene fiber thermally conductive pad according to claim 7, It is characterized in that The S2.2 ultrasonic dispersion is to add the surface-modified and fully fused graphene fibers into N,N-dimethylformamide DMF solvent, add dispersant polyvinylpyrrolidone PVP, and perform ultrasonic dispersion for 3-4 hours to form a uniform dispersion.
9. The method for preparing the graphene fiber thermal conductive pad according to claim 8, It is characterized in that During the ultrasonic dispersion process S2.2, circulating cooling is introduced to control the solution temperature at 20-30° C. to prevent excessive temperature from affecting the dispersion effect and material properties.
10. The method for preparing the graphene fiber thermal conductive pad according to claim 4, It is characterized in that The multi-level pore structure of the S4.3 graphene fiber is formed by high temperature annealing at 800-1000° C. for 2 hours to form micron-sized pores inside the fiber, thereby forming a graphene fiber with a multi-level pore structure.
